Use of photometric data in laboratory work on astronomy (Pedagogy of Higher and Secondary Education, 2012)
Malchenko S. L., Riznichenko T.O. Use of photometric data in laboratory work on astronomy.This paper shows the necessity of a laboratory work on a lesson of astronomy. The development of laboratory work on the theme «The photometric study of stars in stellar clusters» is presented. The purpose of this work: the photometric data catalog system Aladin have used for the study of stellar clusters and search of variable stars and the «background stars».
Keywords: laboratory work of astronomy; photometric data; stellar clusters; variable stars